PUBLISITAS POLITIK SEBAGAI UPAYA STRATEGI KOMUNIKASI POLITIK KANDIDAT PILKADA DKI JAKARTA TAHUN 2017 - Pia Khoirotun Nisa (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This paper attempts to explain Political Communication Strategy and Publicity Politics Jakarta governor candidate in local elections in 2017 DKI basically political communication and political publicity aims to increase the popularity and elektabilitas in the eyes of the public to take sympathy. There are various ways to increase the popularity and elektabilitas that is by utilizing naturally regular occurrence (pure publicity), utilizing extraordinary events (tie-in publicity), the third utilize the activities carried out third party (free ride publicity), and the latter publicity who buy space in the media (paid publicity). In the context of the elections, political communication strategies have a central role in the agenda of victory. A candidate in this case is not only relying on the popularity and position as incumbent candidate, but there are political communication strategies that can be applied in accordance with the conditions and the place where the contestation is held. There are three important things in political communication strategies must be owned the candidates are: First, social capital (Social Capital), Second, have the financial support, the Third, Network (Network). This network is divided into two: first, community networks, such as the majlis taklim, farmers and other community groups. Second, networks are deliberately formed.